Leveraging Resources And Capabilities To Enhance Organizational Resilience In The Malaysian Manufacturing Sector - Vengirasamy, Shela (2024)
The modern manufacturing industry is confronted with constant disruptions, resulting in severe distress to managers and employees alike. As a key contributor that accounts for a sizable portion of the world’s GDP and employment, the industry is highly impacted from such regular disruptions that challenge its resilience. Thus, the present study develops a comprehensive theoretical model explicating key resources and capabilities of firms that can promote organizational resilience; and validates the model in the context of the Malaysian manufacturing sector. The research model builds on the theoretical foundation of Resource-based View (RBV) and empirically tested using Partial Least Squares-Structural Equation Modelling (PLS-SEM) on a sample of 217 manufacturing firms in Malaysia. The analysis yielded three salient findings. First, several strategic resources and capabilities including financial resources availability, human capital, IT infrastructure flexibility, and collective mindfulness positively influence organizational resilience. Conversely, improvisation capability and risk management culture do not show a significant effect on organizational resilience. Second, improvisation capability does not moderate the relationships between resources and organizational resilience as theorized. Third, social capital and transformational leadership indirectly influence organizational resilience through the mediating effect of collective mindfulness. These findings provide vital theoretical implications for the current body of knowledge of organizational resilience and practical implications for managers as well as policy makers.